Radical nephrectomy performed by open, laparoscopy with or without hand-assistance or robotic methods by the same surgeon produces comparable perioperative results - Tanya Nazemi; Anton Galich; Samuel Sterrett; Douglas Klingler; Lynette Smith; K.C. Balaji (International Brazilian Journal of Urology, 2006)
PURPOSE: Radical nephrectomy can be performed using open or laparoscopic (with or without hand assistance) methods, and most recently using the da Vinci Surgical Robotic System. We evaluated the perioperative outcomes using a contemporary cohort of patients undergoing radical nephrectomy by one of the above 4 methods performed by the same surgeon. MATERIALS AND METHODS: The relevant clinical information on 57 consecutive patients undergoing radical nephrectomy from September 2000 until July 2004 by a single surgeon was entered in a Microsoft Access DatabaseTM and queried. Following appropriate statistical analysis, p values < 0.05 were considered significant. RESULTS: Of 57 patients, the open, robotic, laparoscopy with or without hand assistance radical nephrectomy were performed in 18, 6, 21, and 12 patients, respectively. The age, sex, body mass index (BMI), incidence of malignancy, specimen and tumor size, tumor stage, Fuhrman grade, hospital stay, change in postoperative creatinine, drop in hemoglobin, and perioperative complications were not significantly different between the methods. While the estimated median blood loss, postoperative narcotic use for pain control, and hospital stay were significantly higher in the open surgery method (p < 0.05), the median operative time was significantly shorter compared to the robotic method (p = 0.02). Operating room costs were significantly higher in the robotic and laparoscopic groups; however, there was no significant difference in total hospital costs between the 4 groups. CONCLUSIONS: The study demonstrates that radical nephrectomy can be safely performed either by open, robotic, or laparoscopic with or without hand assistance methods without significant difference in perioperative complication rates. A larger cohort and longer follow up are needed to validate our findings and establish oncological outcomes.